I am Malala : the girl who stood up for education and was shot by the Taliban - Yousafzai, Malala, 1997- (New York : Little, Brown and Company, 2013)
Describes the life of the young Pakistani student who advocated for women's rights and education in the Taliban- controlled Swat Balley, survived an assassination attempt, and became the youngest nominee for the Nobel Peace Prize.
A daughter is born -- My father the falcon -- Growing up in a school -- The village -- Why I don't wear earrings and Pashtuns don't say thank you -- Children of the rubbish mountain -- The mufti who tried to close our school -- The autumn of the earthquake -- Radio Mullah -- Toffees, tennis balls, and the Buddhas of Swat -- The clever class -- The bloody square -- The diary of Gul Makai -- A funny kind of peace -- Leaving the valley -- The Valley of Sorrows -- Praying to be tall -- The woman and the sea -- A private Talibanization -- Who is Malala? -- "God, I entrust her to you" -- Journey into the unknown -- "The girl shot in the head, Birmingham" -- "They have snatched her smile" -- One child, one teacher, one book, one pen.
Keywords: Yousafzai, Malala, -- 1997-; Young women -- Education -- Pakistan; Young women -- Pakistan -- Biography; Children's rights -- Pakistan -- Biography